DINAMIKA HUBUNGAN ANTAR UMAT BERAGAMA: “STUDI KASUS PENANGANAN KONFLIK UMAT BUDDHA TRI DHARMA DENGAN KONGHUCU (MAKIN)” KECAMATAN PEMANGKAT KABUPATEN SAMBAS KALIMANTAN BARAT - Ibnu Hasan Muchtar (Harmoni, 2014)
This study aimed to describe the disputes between the believer of Confucian and Buddha Tri Dharma, dispute resolution which used, contributing factors and limitation factors on resolving the dispute. The results showed that the way of conflict resolution which did by the Government of Pemangkat district using persuasive approach, inventory problems, internal meetings of MUSPIKA officials with the officials of the Office of Religious Affairs, and mediation both parties involved in the conflict so that disputes could be minimized eventhough its still unfinished yet. While, preventive measures that should be chosen is forming joint committee for the celebration of the Chinese New Year and Cap Go Meh ceremonies in the future. One of the contributing factors is consciousness among the leaders of both communities to resolve the disputes and conflict. One of the limitation factors: there is no certainty about the distinction of both: the name and ornament of worship place, rituals and way of worship of both.